Determinants of Sustainability Reporting: Profitability, Board of Directors, Audit Committee, and Firm Size in SRI-KEHATI - Haifa Pasya Razamah; Frido Saritua Simatupang (Yayasan Sinergi Kawula Muda, 2026)
Using firm size as a moderating factor, this study looks at how profitability, the board of directors, and the audit committee affect sustainability report disclosure. It stems from rising deforestation rates, which have intensified regulatory and stakeholder pressures and encouraged firms to enhance sustainability reporting as corporate accountability, despite conflicting findings in prior research. This study focuses on companies listed on the SRI-KEHATI Index during the 2022-2024 period, which reflects regulatory developments in sustainability reporting. Using a quantitative methodology, panel data from financial, sustainability, and annual reports of 12 corporations chosen by purposive sampling were analyzed. Panel data and Moderated Regression Analysis (MRA) using EViews 13 are used in this regression analysis. The results show that the audit committee, board of directors, and profitability have no partial influence on the disclosure of sustainability reports. Nonetheless, it was discovered that firm size had a negative moderating effect on the association between the board of directors and sustainability reporting and a positive moderating effect on the relationship between profitability and sustainability reporting. Firm size moderates the effect of audit committees insignificantly. This study concludes that Firm size is an important factor in determining sustainability disclosure practices. The findings indicate that, based on the sampled SRI-KEHATI companies during the 2022-2024 period, firm size is empirically associated with the extent of sustainability information disclosure. Companies are advised to optimize governance and pay attention to operational scale in improving the quality of sustainability disclosure.